Everything in negotiable - "Kennedy, Gavin" (London, 1982)
The topics and issues that are discussed in this book feature in my international negotiating seminar entitled: Everything is Negotiable! I have been running this seminar( and its workshop version) since 1980 and it has been attended by managers in and from Scandinavia, Britain, Continental Europe, North America, the Middle and Far East, and Australia. May managers who attend the seminars- particularly the Negotiators' 'Confessional' and 'Clinics'- revise their negotiating approach afterwards. But not all need to do so: some return to their work more than refreshed having had their individual approaches endorsed!
Keywords: Negotiation